Relative Bioavailability of a Paediatric Granule Formulation of the HIV Integrase Inhibitor Dolutegravir in Healthy Adult Subjects. Issue 3 (April 2014) - Patel, Parul; Song, Ivy; Borland, Julie; Chen, Shuguang; Peppercorn, Amanda; Wajima, Toshihiro; Funaki, Takeshi; Fujita, Naomi; Hughes, John; Piscitelli, Stephen
Background: This study evaluated the pharmacokinetics of a granule formulation of dolutegravir developed as an alternative to tablets for use in paediatric populations. Methods: A randomized, open-label study in healthy adults was carried out. Subjects received five treatments in a crossover design: a single dose of dolute-gravir 50 mg as a tablet and dolutegravir 50 mg in 10 g of granule administered directly to mouth or mixed with purified water, water containing high cation concentrations or milk-based infant formula. Study treatments were separated by 7 days. Safety evaluations and serial pharmacokinetic sampling were done during each treatment period. A non-compartmental pharmacokinetic analysis was performed; geometric least-squares mean ratios and 90% CIs were generated for treatment comparison. Palatability was assessed by questionnaire. Results: Plasma dolutegravir exposures in all granule treatment arms exceeded those of tablet formulation. The mean area under the curve from time 0 to infinity (AUC0–∞ ) and maximum concentrations were 55–83% and 62–102% higher, respectively. Pharmacokinetics were similar when dolutegravir was mixed with purified or cation-containing water. Dolutegravir was well tolerated, with no withdrawals due to adverse events. Taste was rated acceptable for all treatments. Conclusions: The exposure of dolutegravir after administration of granule formulation alone, with different types of water and with milk formula, exceeded that of the tablet. The similarity of dolutegravir exposure seen with the granule formulation demonstrates that dolutegravir granule can be given without restriction on the type of liquid or can be administered directly to the mouth (for example, when potable water is not available).